Building a simulator of a traffic assignment model for the use of public transportation in the sector "corredor calle 5 (2017)
Worldwide, the rise in the population has created the need to develop efficient transportation systems in order to facilitate the movement of citizens. Nowadays the main public transportation in the city of Cali is called "Masivo Integrado de Occidente" MIO. The waiting times on the system are high and the capacity of the buses is often exceeded. For this reason, it is necessary to analyze the system to create different scenarios where the current situation could be improved. This project was designed to develop a simulator for the use of public transportation in "Corredor Calle 5", one of the main sectors in the city, in order to support the decision-making process on the traffic assignment for the MIO system. Throughout the simulations it was possible to determine that it is necessary to change the synchronization of traffic lights prioritizing the buses traffic, with the purpose of reduce the users waiting time.